Acknowledging Anti‐Blackness, Overlooking Anti‐Asian Racism: Missed Developmental Opportunities for Chinese American Youth. (3rd April 2022) - Lee, Helen; Lei, Quinmill; Su, Grace; Zhang, Sara
Abstract : This paper explores the pathways and barriers to critical consciousness development for Chinese American youth. Thirty‐five interviews conducted in 2020 with high‐school‐aged students in Chicago were analyzed to better understand young people's experiences developing an understanding of anti‐Asian racism and anti‐Blackness. Results indicated that participants overwhelmingly engaged in sustained conversations about Black Lives Matter and/or made efforts to address anti‐Blackness within their families, but engaged in limited conversations about anti‐Asian racism. Furthermore, conversations at home and school often failed to contextualize anti‐Asian racism, specifically in relation to the experiences of other oppressed groups. Findings highlight a need for research on and practice with Chinese American adolescents to recognize the unique racial positioning of Asian Americans under White supremacy.